Diagnosis for a maintenance proposal of the Macuto bridge in the city of Barquisimeto (Gaceta Técnica, 2024)
The Macuto Bridge is located on Nectario María Avenue in the Iribarren Municipality of Lara State, over the Turbio river, in the city of Barquisimeto, Venezuela, being the main access route to the communities of El Roble, Macuto, El Manzano and Río Claro. The actual conditions of the bridge alert the population, who are cautious given the event of April 9, 1999 where 8 people lost their lives when they fell with the previously located bridge, due to a flooding of the river. Added to this is the structural conditions in which it was found, among them the lack of maintenance stands out, in short, resulting in the collapse of the structure caused by the inability to support the acting loads. For this reason, a preliminary inspection study was carried out, with the purpose of identifying the visible and accessible faults of the Macuto bridge, in order to alert the competent authorities to become aware of its state of conservation and to be able to plan the necessary actions. . Based on the preliminary inspection, a maintenance proposal presented in this work was made, since it was concluded that the origin of some failures is the result of the lack of application of conservation programs for the structure
Keywords: survey of fault symptoms; environmental actions on structures; maintenance of works; Macuto bridge; transportation infrastructure; bridge maintenance